PENINGKATAN HASIL BELAJAR SISWA DENGAN STRATEGI PEMBELAJARAN ACTIVE DEBATE MATA PELAJARAN PKN KELAS V SD 163098 KOTA TEBING TINGGI - Parida Simbolon (PGSD Universitas Negeri Medan, 2016)
This purposes of this research is to improve learning result on PKn subject through active sebate strategy. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class V, SD N 163098 Tebing Tinggi which amounted to 34 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of PKn subjects can improve student learning result characterized by increased mastery learning students, namely cycle I (79.41%), cycle II (88.23 %) and complete learn the clasical equal to 88.23 %. Key Word : Learning result, Active debate straategy.